Quality assurance of aquatic foods - Jeyasekaran, G.; Shakila, R. Jeya. (Abingdon, Oxon ; New York : CRC Press, 2021)
This book deals with the quality and safety of aquatic food. It focuses clearly on biological and chemical hazards, antibiotic and pesticide residues, and heavy metal contaminants associated with aquatic food. The quality problems in various aquatic food products and their methods of assessment are exhaustively dealt in this book. Besides, food quality management systems like HACCP, SSOP, SCP, GHP, GMP have also been explained for easy adoption. The International and National Standards prescribed by FSSAI, EIC, BIS, Codex, USFDA, ISO and EU for aquatic food products are explicitly given. It is also useful to the personnel of aquatic food industries to improve their working knowledge on maintaining the quality and safety aquatic foods. Note: T& F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
1. Introduction 2. Quality of Aquatic Food 3. Hazards in Aquatic Food 4. Quality Problems in Aquatic Food Products 5. Methods of Assessing Quality of Aquatic Food 6. HACCP for Aquatic Food Industries; 7. Plant Sanitation and Hygiene 8. Standards for Aquatic Foods
OCLC-licensed vendor bibliographic record.
Keywords: Fishery products -- Quality control; Aquatic resources -- Quality control; TECHNOLOGY / Food Science